Fatty acid addition strategy redirected the metabolic flux towards an ultra-high monensin productivity of Streptomyces cinnamonensis - Shanfei Zhang; Qingming Hou; Zhenhua Wang; Dandan Tian; Xianyuan Zhang; Yan Zhang; Qun Wu; Fubao Sun (Synthetic and Systems Biotechnology)
Monensin, a polyether ionophore antibiotic produced by Streptomyces cinnamonensis, exhibits notable anticoccidial and antitumor properties. In this study, a fatty acid addition (FAA) strategy significantly enhanced the monensin production capability of S. cinnamonensis, resulting in an unprecedented monensin titer of 17.72 g/L at 192 h, 7.36 times that of the control. Physiological assay showed the FAA markedly altered the cellular morphology, cell membrane fluidity, enzymatic activity and intracellular cofactors, thus indicating of an increased carbon flux. With transcriptional analysis at the product biosynthesis phase, 4 genes in the monensin biosynthesis cluster and 11 genes related to the oxidative stress response were observed to be upregulated. Meanwhile, genes consisting of two sugar transport systems were downregulated. For the precursors supply, genes associated with triacylglycerols (TAG) degradation (lps) and fatty acid degradation genes (fadE, fadB, fadA) were upregulated, while genes to TAG synthesis were downregulated. For the monensin synthetic pathway, 8 polyketide synthase genes, 9 modifier genes and 3 pathway-specific regulatory genes within the monensin biosynthetic gene cluster (mon) were upregulated. Consequently, the physiological and transcriptional response of S. cinnamonensis to the FAA strategy was correlated well with the monensin biosynthesis. The findings not only elucidated the de novo biosynthesis of monensin via FAA, but also offered a strategic framework for efficient production of polyketide natural products.